Сборник рассказов Шляхтич Завальня, или Беларусь в фантастичных повествованиях Яна Барщевского в контексте русской готической прозы - Macapura, Liudmila (Acta Polono-Ruthenica, 2018)
The article deals with the collection of stories by J. Barszczewski Nobleman Zawalnia, or Belarus in Fantastic Stories (Szlachcic Zawalnia czyli Białoruś w fantastycznych opowiadaniach, 1844-1846) in the context of Gothic literary tradition in Russian literature of the 30-40-es of the XIXth century. The author comes to the conclusion that folk motives in the cycle Nobleman Zawalnia... transform under the influence of Gothic literary tradition, which could be perceived by J. Barszczewski indirectly, through the oeuvre of other authors. The usage of comparative methods allows to find out typological relations between the cycle by Barszczewski and the cycles of stories Evenings on a Farm near Dikanka by N. V. Gogol and An Evening on Khoper by M. N. Zagoskin.